Subcellular shifts of trimeric G-proteins following activation of baker's yeast by glucose - Kotyk, A; Ihnatovych, I; Lapathitis, G; Lamash, N; Svoboda, P (Folia microbiologica, 2001)
Addition of glucose to a resting cell suspension of the yeast Saccharomyces cerevisiae was accompanied by marked shifts of the G alpha-protein subunits from the plasma membrane to the cell interior. This process was rapid with half-times between < 10 and 20 s. The decrease of the plasma membrane pool of the Gi alpha/Go alpha- and Gq alpha/Gl 1 alpha-protein subunits correlated with an increase in acid-sensitive forms of these proteins which was recovered in the mitochondrial and/or lysosomal membrane fraction. In contrast to cells from higher organisms glucose-stimulated yeast exhibits an extremely rapid type of the redistribution (internalization). The question remains open as to the functional significance of the internalized forms of the G-proteins as these remain sequestered from the plasma membrane well after glucose has been consumed.
Keywords: Subcellular Fractions; Saccharomyces cerevisiae; glukosa; Glucose; GTP-Binding Proteins; subcelulární frakce; proteiny vázající GTP; imunoblotting; Immunoblotting